DEIXIS AND PRAGMATIC STRATEGIES IN LILO & STITCH (2025): AN ANALYSIS THROUGH LEVINSON’S FRAMEWORK - Karamoy, Indriany Fera; Roya , Natasya Abelia; Mogea, Tini; Pabur, Herminus Efrando (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
Deixis has an important role in communication by allowing speakers and listeners to locate referents, events, and actions within a specific context. In real life interactions, deictic expressions help participants identify who is involved, when events occur, and where actions take place, thereby ensuring clarity and coherence in discourse. Similarly, in staged or fictional conversations, such as cinematic dialogue or film, deixis is essential for expressing social relationships, emotional states, and character identities. Through the use of deictic forms, speakers convey not only the literal meaning of their utterances but also pragmatic and interpersonal nuances that shape audience understanding and engagement within the narrative. The aims of this study were to identify the types of deixis found in Lilo & Stitch (2025) and to analyze their pragmatic strategies in conveying emotional and social meanings in the utterances of the main characters, Lilo and Stitch. A qualitative descriptive approach was employed, using the documentation method to collect data from the film’s transcript. The data were analyzed using Levinson’s model of deixis, which includes personal, spatial, temporal, discourse, and social categories. The results showed that personal deixis was the most frequently used type, functioning to express personal identity, emotional closeness, and character relationships. Spatial and temporal deixis provided contextual anchoring of events, while discourse deixis maintained narrative coherence and thematic progression. Social deixis appeared less frequently but indicated respect, intimacy, and family hierarchy among characters. Overall, deixis in Lilo & Stitch (2025) served not only as a linguistic reference system but also as a pragmatic strategy that reflected belonging, empathy, and cross-species communication. The findings implied that cinematic dialogue can be an effective medium for studying pragmatic meaning, offering insights for linguistic studies and language education.